2022
DOI: 10.1186/s12888-022-04012-z
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of current and lifetime sexual hallucinations and delusions in Lebanese patients with schizophrenia: frequency, characterization, and association with childhood traumatic experiences and disease severity

Abstract: Background Till that date, a sparse body of research has been dedicated to perusing psychotic symptoms of sexual type, particularly in psychiatric populations. Our study’s objective was to delineate psychotic symptoms with a sexual content, namely sexual delusions and hallucinations, among inpatients diagnosed with schizophrenia in Lebanon, and scrutinize their relationships with the severity of schizophrenia symptoms and childhood abusive events. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…91,92 Other reasons for expecting sexual hallucinations in borderline personality disorder are (1) the relatively high prevalence of sexual trauma, with rates varying from 26% to 71%, (2) the strong association between (sexual) trauma and sexual hallucinations in other patient groups, 1 and (3) the repeated and consistent finding that individuals with borderline personality disorder also experience other types of hallucinations, with prevalences ranging from 13% to 60%. 1,12,29,[93][94][95] These findings are at odds with the traditional views that hallucinations are rare in borderline personality disorder and that at their worst they are of a fleeting and self-limiting nature. And yet the studies cited indicate that hallucinations in this group are phenomenologically indistinguishable from those experienced by people with a schizophrenia spectrum disorder, that certainly not all of them are of a fleeting nature, and that the burden they may cause is often high.…”
Section: Miscellaneousmentioning
confidence: 78%
See 2 more Smart Citations
“…91,92 Other reasons for expecting sexual hallucinations in borderline personality disorder are (1) the relatively high prevalence of sexual trauma, with rates varying from 26% to 71%, (2) the strong association between (sexual) trauma and sexual hallucinations in other patient groups, 1 and (3) the repeated and consistent finding that individuals with borderline personality disorder also experience other types of hallucinations, with prevalences ranging from 13% to 60%. 1,12,29,[93][94][95] These findings are at odds with the traditional views that hallucinations are rare in borderline personality disorder and that at their worst they are of a fleeting and self-limiting nature. And yet the studies cited indicate that hallucinations in this group are phenomenologically indistinguishable from those experienced by people with a schizophrenia spectrum disorder, that certainly not all of them are of a fleeting nature, and that the burden they may cause is often high.…”
Section: Miscellaneousmentioning
confidence: 78%
“…Blom and Mangoenkarso 1 found a one-year prevalence of 1.7% in 778 clinical patients, while Small and colleagues 28 reported a rate of 4% for 50 recently hospitalized patients. In a group of 167 chronically hospitalized patients, Gerges and colleagues 29 recently found a current rate of 21%, and in a similar group of 113 patients, Lyketsos and colleagues 30 earlier computed a current rate of 19.5%. In their study, Gerges and colleagues 29 mention a lifetime prevalence of 30.5%, whereas five decades earlier in a similar but entirely female population, Gittleson and Dawson-Butterworth 25 found a lifetime prevalence of 44% for genital hallucinations.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Not to forget the role of culture in severe mental illnesses such as schizophrenia which requires adequate attention and continued research [ 55 ]. An anterior Lebanese study aimed to delineate psychotic symptoms with sexual content, along with their relationships with the severity of schizophrenia symptoms and childhood abusive events [ 56 ]. They found that 36.5 and 50.3% of the participants screened positive for current and lifetime episodes of sexual delusions and/or hallucinations, respectively [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…An anterior Lebanese study aimed to delineate psychotic symptoms with sexual content, along with their relationships with the severity of schizophrenia symptoms and childhood abusive events [ 56 ]. They found that 36.5 and 50.3% of the participants screened positive for current and lifetime episodes of sexual delusions and/or hallucinations, respectively [ 56 ]. Another cross-sectional study examined a sample of Lebanese patients with schizophrenia to identify clinical risk factors for aggressiveness including child abuse.…”
Section: Introductionmentioning
confidence: 99%